ANALISIS PERUBAHAN URBAN HEAT ISLAND DAN PENGARUHNYA TERHADAP INDEKS KENYAMANAN KOTA BANJARBARU - Saragih, Ruth Mandasari; Rusmayadi, Gusti; Adriani, Dewi Erika; Nugroho, Yusanto (Universitas Lambung Mangkurat, 2024)
The Banjarbaru administrative status has changed from an Administrative City to a City, and in 2022 become the Provincial Capital. Population growth and infrastructure/building development due to these changes may affect environmental changes. A significant increase in air temperature against its normal due to environmental changes can trigger climate change. Urban Heat Island (UHI) is a phenomenon recognized by the higher temperature conditions in urban areas compared to surrounding areas. UHI identification is known by calculating the difference in Land Surface Temperature (LST) values using remote sensing (satellite data). An increase in the value of LST in an area can trigger the appearance of UHI and make the environment less comfortable. The LST value is also related to population, vegetation, residential areas, and built-up land. Thermal Humidity Index (THI) is an index used to determine comfort level based on temperature and humidity conditions. This study aims to analyze spatiotemporal changes in UHI phenomena in the Banjarbaru area during three administrative status periods (1998 - 2022) and its effect on the comfortable index. This study uses Landsat satellite data (consist Visible, Near Infrared, and Thermal Bands) and Relative Humidity (RH) from 2 weather stations in Banjarbaru. The result shows that the distribution of UHI in the Banjarbaru City area increases around industrial areas, settlements, government centers, and along arterial roads that are open land without trees. In general, the Banjarbaru area experienced an increase in the comfort index. Initial conditions belonging to the comfortable and less comfortable classes changed to become less comfortable to uncomfortable, especially in the North Banjarbaru sub-district and around Syamsudin Noor Airport ( Landasan Ulin sub-district).